Loss of Child Custody to a Father - Mohamad Rizaldi Fitra Abadi; Nirwan Junus; Suwitno Yutye Imran (Universitas Negeri Gorontalo, 2023)
This study aims to determine the transfer of child custody to a father. The method used in this study is normative research methodology and uses a statutory and shirt approach as well as descriptive analysis techniques. The results of this study indicate that according to the Compilation of Islamic Law, the custody of a child to a father after a divorce is the right of the mother to take care of a child who is not yet mumayyiz or not yet 12 (twelve) years old. But if you look at the contents of decision number 448/Pdt.G/2018/PA. But where the judge imposes child custody on a father, after analysis that the judge does not only refer to the applicable laws and regulations, but the judge has the authority to assess, analyze and decide under the facts presented in court and prioritize the interests and welfare of children.